(untitled) (Ágora UNLaR, 2019)
A partir del análisis de la obra Réquiem para cuatro llorones de Julio Contreras Oliva, podemos reflexionar el modo en el que el autor/director emprende su camino de creación desde la acción de manera intermitente entre la presentación y la representación de sus personajes, quienes ponen en evidencia el pathos que aflora de sus cuerpos en su estado más profundo de tristeza, pasión y padecimiento. Poniéndonos en consonancia con la revalorización del cuerpo-materia y los cambios en los modos de concebir y organizar su noción del cuerpo en las sociedades occidentales contemporáneas, nos proponemos realizar un breve análisis sobre la significación del cuerpo en la Danza y el Teatro en relación a lo que ésta obra deja traslucir. CONSIDERATIONS FROM THE WORK RÉQUIEM PARA CUATRO LLORONES (2010) BY JULIO CONTRERAS IN RELATION TO THE IDEA OF THE FEMININE IMAGERY OF THE TRAGIC ABSTRACT Based on the analysis of the work Réquiem para cuatro llorones (Requiem for Four Whiners) by Julio Contreras Oliva, we can reflect on the way in which the author / director embarks on his journey of creation through intermittent action between the presentation and representation of his characters, who reveal the pathos that emerges from their bodies in their deepest state of sadness, passion and suffering. Putting ourselves in line with the revaluation of the body-matter and the changes in the ways of conceiving and organizing its notion of the body in contemporary western societies, we propose to make a brief analysis about the meaning of the body in dance and theater in relation to what this work shows. Key words: Julio Contreras Oliva, presentation, representation, feminine tragic imagery, body, dance and theater